Literasi Digital Pada Pelaku UMKM di Kecamatan Anyer, Program Pengembangan Mitra Binaan Fakultas Ekonomi dan Bisnis Islam - Ansori, Aan; Noeralamsyah , Zenno; Surahman (Pusat Pengabdian Kepada Masyarakat Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Abstract: This research aims to assess the level of digital literacy among Micro, Small, and Medium Enterprises (MSMEs) in the Anyer District. Digital literacy has become a crucial aspect in the era of increasing digitalization that dominates the business world. Knowledge and application of digital technology can provide competitive advantages for MSMEs to grow and adapt to the dynamic business environment. The research findings indicate that the majority of MSMEs in the Anyer District have limited levels of digital literacy. While most respondents have internet access, the utilization of digital technology for expanding business networks, product marketing, and financial management remains underutilized. Based on these findings, it is recommended that local government and relevant agencies provide training and guidance programs on digital literacy for MSMEs in the Anyer District..